MODERN APPROACHES TO TREATMENT OF COMORBID PATHOLOGY BRONCHOPULMONARY AND THE CARDIOVASCULAR SYSTEM - Moiseeva, N.V.; Vakhnenko, A.V.; Rumyantseva, M.O. (World of Medicine and Biology, 2016)
Chronic obstructive pulmonary disease is a weighty social health and economic importance, and remains one of the major causes of morbidity and mortality worldwide. Presently, special attention is paid to comorbid conditions, when the patient has a combination of pathology respiratory and cardiovascular systems. This research has been devoted to finding ways to optimize the treatment of moderate acute exacerbations of chronic obstructive pulmonary disease with the complication of bronchoectasis on the background of arterial hypertension.